An evaluation of the Cape Townships Ordinance, no. 33 of 1934, as amended - Binedell, O B (School of Architecture, Planning and Geomatics, 2020)
Accepting that there may be scope for improvement, the goal of this thesis is to evaluate in certain depth the performance of the Cape Townships Ordinance against the background of present day 6. development pressures and a sound approach to planning. The subject is tackled by presenting "Ideals to strive for", "The status quo", "An evaluation", "Remedies" and a 'Summary". Map No.1 orientates the reader geographically to the Cape Province in which the Ordinance functions.